Analisis Keterampilan Kemandirian Makan dan Minum Anak Tunanetra di TK Sarena Jaya - Heni Farida; Hijriati Hijriati; Cut Salfitri Ria; Rozah Rozah; Masri Rafita (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
Children with visual impairments face challenges in developing independence in daily activities such as eating and drinking. This study, conducted at TK Sarena Jaya, aimed to analyze the independence skills of visually impaired children in eating and drinking. The findings revealed that visual impairment can lead to social barriers, self-doubt, and dependency on others. Strategies such as providing safe movement stimulation, developing orientation skills, and promoting self-confidence were identified as crucial in supporting these children. Additionally, the use of assistive technologies and social education for both children and society were highlighted as essential for enhancing independence and social integration. Overall, a holistic approach is necessary to empower visually impaired children to navigate daily tasks independently and thrive socially.